Destrezas discursivas de docentes de la Carrera de Pedagogía, modalidad presencial. - Nava Nava, Claribel Del Valle (2016)
Teaching includes a large number of tasks within the educational process. One of them is the mediation between students and learning; within the process of teaching and learning a good communication is essential. The methodology used by the teacher should encourage the interest and attention of the students; in addition, a proper verbal and non-verbal communication is necessary so the process does not get hind. This is the reason why the used speech facilitates or hinders educational work. This study has sought to characterize the educational speech, focusing on management discursive strategies of sixteen teachers who belong to the School of Education at the Salesian Polytechnic University - Headquarters Quito. As a result, the research promotes a horizontal strategy between teacher-student interaction, those who explore the prior knowledge of the student, looking to establish shared plots of knowledge. However it is evident a lack of discursive strategies allowing a mayor construction of knowledge by a deep argumentation of the topics in question.